Micropropagation on multiplication of native greenberries in South of Brazil (Research, Society and Development, 2021)
Rubus brasiliensis and Rubus erythroclados are commonly known as greenberries. This work aimed to test in vitro micropropagation protocols to greenberries. The multiplication experiment was conducted using BAP at concentrations 1 mg L-1, 2 mg L-1 and 3 mg L-1. The rooting experiment was carried out in ½ MS medium without the addition of hormones, using 0.1 mg L-1 NAA or 1.0 mg L-1 IBA. The highest rate of viability of explants was obtained with R. brasiliensis propagation using 1.0 mg L-1 of BAP. Rooting explants showed survival rates higher than 85%. Rooting rates in R. erythroclados was 87% while in R. brasiliensis it was 38%, The highest rates were obtained using 1.0 mg L-1 IBA in R. erythroclados.The acclimatization reached survival rates of 75% when rooted using NAA and ½ MS and 86% when rooted with IBA. In vitro culture shows to be a viable method to propagate greenberries.